New Insights of Salicylic Acid Into Stamen Abortion of Female Flowers in Tung Tree (Vernicia fordii) - Liu, Meilan; Li, Wenying; Zhao, Guang; Fan, Xiaoming; Long, Hongxu; Fan, Yanru; Shi, Mingwang; Tan, Xiaofeng; Zhang, Lin (Frontiers in Genetics, 2019)
Tung tree (Vernicia fordii), an economically important woody oil plant, is a monoecious and diclinous species with male and female flowers on the same inflorescence. The extremely low proportion of female flowers leads to low fruit yield in tung orchards. The female flower normally develops along with stamen abortion; otherwise sterile ovules will be produced. However, little knowledge is known about the molecular basis of the female flower development in tung tree. In this study, integrated analyses of morphological and cytological observations, endogenous phytohormone assay and RNA-seq were conducted to understand the molecular mechanism of the female flower development in tung tree. Cytological observation suggested that the abortion of stamens in female flowers (SFF) belongs to the type of programmed cell death (PCD), which was caused by tapetum degeneration at microspore mother cell (MMC) stage. A total of 1,366 differentially expressed genes (DEGs) were identified in female flowers by RNA-seq analysis, of which 279 (20.42%) DEGs were significantly enriched in phenylpropanoid biosynthesis, phenylalanine metabolism, flavonoid biosynthesis, starch and sucrose metabolism, and plant hormone signal transduction. Stage-specific transcript identification detected dynamically expressed genes of important transcription regulators in female flowers that may be involved in PCD and floral organ development. Gene expression patterns revealed that 17 anther and pollen development genes and 37 PCD-related genes might be involved in the abortion of SFF. Further analyses of phytohormone levels and co-expression networks suggested that salicylic acid (SA) accumulation could trigger PCD and inhibit the development of SFF in tung tree. This study provides new insights into the role of SA in regulating the abortion of SFF to develop normal female flowers.